The Rational Rebel: How Rational, How Rebellious? Some African Examples - Buytenhuys, Rob (Afrika Focus, 1996)
My aim in this article is to evaluate some general statements on civil violence, and more particularly on the purposefulness of collective action and on the alleged rationality that moves social actors launching rebellion. With the use of African examples, examples that are too seldom taken into account in theoretical explanations of violent conflict, it is shown that rationality in collective action can certainly not be dismissed out of hand, but that some caveats have to be entered into the argument: some African rebels, although acting rationaly, base themselves on completely erroneous information, while in other cases social actors consciously opt for life or a career as a rebel, but out of motives that anything but "revolutionary ". KEY WORDS: Civil violence, Rational choice theory, Africa South of the Sahara.